An Analysis Of The Implications Of Commercialization In School Education And Its Consequences On Higher Education - Ping, Li; Paramalingam, Muhantha (Journal of Neonatal Surgery, 2025)
Examining privatization's impact on K-12 and higher education, this research aims to understand how it affects educational equity, accessibility, quality, and long-term outcomes. School privatization has led to the proliferation of private schools, which promote a higher-quality education but may exacerbate economic disparities. Examining how privatization has altered resource distribution, curriculum adaptability, teacher quality, and the widening socioeconomic performance gap, this research examines the ripple effects throughout the education system. While public schools struggle with insufficient funding, which impacts the quality of education available to kids from lower-income homes, private schools cater to children from middle-class and higher-income backgrounds, according to the report. This study examines the phenomena of access to higher education and how it has evolved as a result of the commercialization of education and the privatization of universities. The increasing expense of tuition, the market-driven nature of educational institutions, and the dependence on private funding are major concerns for many. The consequences of changing university curriculum on student debt are being investigated. Public and private colleges are becoming more financially and research objective disparate. Through an analysis of case studies, statistics, and interviews with key stakeholders, this study clarifies the many impacts of privatization. Additionally, it provides policy recommendations for achieving educational equity so that all kids may benefit from a high-quality, inclusive education. Finding a happy medium between the public and commercial sectors is at the heart of these recommendations.